The First Salmonella Enteritidis Phage Type 1 Infection of a Commercial Layer Flock in Finland - Johansson, T. M.-L. (Acta Vet Scand, 1996)
The first Salmonella Enteritidis phage type (PT) 1 infection in a commercial layer flock of 2700 birds in Finland occurred in 1995. All the birds were ordered to be killed, the eggs to be destroyed and access to the layer house was denied in order to prevent spread of the infection. Ninety one commercial layers, 61 replacement pullets and 1062 eggs were collected for the analyses. The total infection level of the flock was 8%, concentrated on the 2 older age groups. S. Enteritidis PT1 was isolated from livers (5%), ovaries (2%) and from caeca (3%), of which 2 positive samples were detected with pre-enrichment and 3 without pre-enrichment by cultivation Rambach agar. Eight % of 105 pooled egg samples were positive, of which 2 were detected only from contents and 3 only from shells indicating both oviductal and faecal contamination routes of eggs. The results support the use of the extended sampling procedure in poultry flocks suspected of human food-borne Salmonella outbreaks of invasive serotypes, including not only faecal but also environmental, organ, blood and/or egg samples.